Reinventing the public: a new organization of schools - Fernández Franco, Francisco Javier (Avances en Supervisión Educativa, 2009)
Today more than ever a new structural schedule for schools is necessary to give a suitable response to the increasingly great and rather frustrating rates of educational failure. This major problem just cannot be solved with mere regulation. Educational practice should be improved there where the heart of education really lies: schools and classrooms. Anything but going down to the bases of the educational system will lead to a new failure.